Analisis Perlakuan Akuntansi Atas Perolehan Dan Penyusutan Aset Tetap Dan Pengaruhnya Terhadap Laporan Keuangan - Meylani, Melan; Nurjanah, Yayuk (Jurnal Ilmiah Akuntansi Kesatuan, 2019)
In the treatment of its fixed assets, PT Bahagia Jaya Sejahtera still has a mismatch. The discrepancy is in the recording of the acquisition price of the fixed assets, the company still records the fixed assets based on the purchase price only, while the costs associated with the fixed assets are charged as costs in the period of occurrence, which are charged as administrative and general costs. In addition to those expenses intended to condition the fixed assets so that they are always ready to be used, recorded as administrative and general expenses in the current period, for example in the purchase of fixed assets in the form of machines, PT Bahagia Jaya does not add these costs to the acquisition price of fixed assets. And when calculating depreciation of fixed assets, companies tend to use the straight-line method, whereas there are other methods that can be used to support the company's earnings. From the results of this analysis, it will be known the comparison of the acquisition price of fixed assets and cost allocation as well as the amount of depreciation costs between the company and the SAK regulations. The results of this analysis are presented in the form of comparative financial statements to determine the effect on financial statements. In the income statement, administrative and general costs are recorded to be too high, due to costs that should add to the acquisition value of fixed assets but instead are allocated to administrative and general costs.Thus, to present financial statements especially in Asset accounting treatment, it should be understood and implemented a fixed accounting policy in accordance with financial accounting standards. Keywords: Fixed assets, depreciation, financial statements